Dampak Transformasi Digital terhadap Sistem Manajemen Perusahaan di Alfamart Nangahure - Maria Ayulina Da Noa; Mariana Gresiani Livince Naggo; Iganasius Damianus Nong Kelvin; Mariandus Evanson Sari; Silvana Mariabel Carcia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The continuous development of technology compels companies to consistently adapt to advancements across various aspects of life. Digital transformation has become an essential need for many organizations today as a strategy to improve service quality and operational efficiency. Alfamart, one of Indonesia's leading retail companies, is currently adopting digital transformation in its business processes. The acceleration of digital transformation in Indonesia necessitates the application of digital technology as a basic platform to support the Industry 4.0 ecosystem, leveraging technologies such as the Internet of Things (IoT), big data, artificial intelligence (AI), and augmented reality. This research employs a qualitative approach and descriptive analysis method to evaluate the impact of digital transformation on PT. Sumber Alfaria Trijaya, Tbk (Alfamart), specifically at the Nangahure unit located in Sikka Regency. Analysis is conducted through data reduction, data presentation, and conclusion drawing stages. The research results indicate that the management system at Alfamart Nangahure has been applied in a structured manner and in accordance with the policy standards set by the headquarters. The system includes a well-organized organizational structure, efficient operational management, systematic human resource management, as well as regular evaluation and monitoring processes that support the achievement of store operational targets.